Analisis Struktur Narasi dalam Cerita Rakyat Nusantara : Studi pada Cerita Malin Kundang - Aprilia Vavalin; Firza Afrian Wardana; Rani Putri Khanza (BADAN PENERBIT STIEPARI PRESS, 2025)
This research aims to analyze the narrative structure in Indonesian folklore with a focus on the story